REPRESENTASI KOMUNIKASI BUDAYA “NGARAK PENGANTIN BUAYA PUTIH” DALAM PERUBAHAN SOSIAL MASYARAKAT PADARINCANG - Rahmi Mulyasih; Ahmad Sururi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
As one part of local wisdom, traditional art of Ngarak Pengantin Buaya Putih in Padarincang Village, Serang Regency experienced various dimensions of change in facing social change. The tendency is that people are slowly starting to display the outside culture in the wedding. This indicates a social change in Padarincang society, this social change is characterized by the reluctance of some younger generation to preserve the arts of